Misleading linkage results in an NF2 presymptomatic test owing to mosaicism. Issue 11 (November 1997) - Bijlsma, E K; Wallace, A J; Evans, D G
Abstract : A two generation family with neurofibromatosis type 2 (NF2) is presented in which a family member requested presymptomatic molecular diagnosis. Since the consultand's mother had clinically well defined NF2, he was quoted to be at 50% risk of carrying an NF2 mutation. Mutation screening in the mother did not show the causative mutation and, consequently, presymptomatic testing was based on linkage analysis. This showed that the consultand carried the high risk chromosome 22. Subsequent mutation screening of his clinically affected sister showed a nonsense mutation, R262X in exon 8 of the NF2 gene. The mother turned out to be a mosaic for R262X; the son had not inherited the mutation. Mosaicism may be a common mechanism in NF2 and other autosomal dominant diseases with a high new mutation rate. This may be one explanation for a difference in expression in generations. Caution has to be exercised when giving results based on linkage tests which imply a very high risk to people in the second generation.